Fibrosis Related Inflammatory Mediators: Role of the IL-10 Cytokine Family - Erna Sziksz; Domonkos Pap; Rita Lippai; Nóra Judit Béres; Andrea Fekete; Attila J. Szabó; Ádám Vannay (Hindawi Limited, 2015)
Importance of chronic fibroproliferative diseases (FDs) including pulmonary fibrosis, chronic kidney diseases, inflammatory bowel disease, and cardiovascular or liver fibrosis is rapidly increasing and they have become a major public health problem. According to some estimates about 45% of all deaths are attributed to FDs in the developed world. Independently of their etiology the common hallmark of FDs is chronic inflammation. Infiltrating immune cells, endothelial, epithelial, and other resident cells of the injured organ release an orchestra of inflammatory mediators, which stimulate the proliferation and excessive extracellular matrix (ECM) production of myofibroblasts, the effector cells of organ fibrosis. Abnormal amount of ECM disturbs the original organ architecture leading to the decline of function. Although our knowledge is rapidly expanding, we still have neither a diagnostic tool to detect nor a drug to specifically target fibrosis. Therefore, there is an urgent need for the more comprehensive understanding of the pathomechanism of fibrosis and development of novel diagnostic and therapeutic strategies. In the present review we provide an overview of the common key mediators of organ fibrosis highlighting the role of interleukin-10 (IL-10) cytokine family members (IL-10, IL-19, IL-20, IL-22, IL-24, and IL-26), which recently came into focus as tissue remodeling-related inflammatory cytokines.